Pengaruh Metode Pengukusan Ikan Gabus (Channa striata) yang direndam dengan Ekstrak Jeruk Kunci terhadap Kadar Albumin - Eri Virmando; Hamdani SP Ginting (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Snakehead fish (Channa Striata) is a type of freshwater fish that is widely known by the people of Indonesia. Until now, the use of snakehead fish is still traditionaly explored. The most common method used is to steam or boil snakehead fish meat (Wirawan et al, 2018). The purpose of this study was to determine the effect of the steaming method of snakehead fish (Channa striata) soaked in lime extract on albumin levels. This research design was experimental and was carried out in 2021. The albumin content test in steamed snakehead fish was carried out in the laboratory and the results were analyzed using the T test at α = 0.05. The results of the average test of the percentage of snakehead fish albumin in the intervention group were 0.3369% and 0.7129% in the control group, and the results of the difference test using the independent t-test showed that the p value was <0.05 through steaming with calamansi extract and there was a significant difference between steaming with calamansi extract and the control (regular steaming).